Application of 2D-MoO3 nano-flakes in organic light emitting diodes: effect of semiconductor to metal transition with irradiation1. Issue 11 (7th February 2015) - Dagar, Janardan; Tyagi, Priyanka; Ahmad, Razi; Singh, Rashmi; Sinha, O. P.; Suman, C. K.; Srivastava, Ritu
<x xml:space="preserve">Abstract</x> Current work demonstrates application of 2D molybdenum oxide nano-flakes as hole injection layer in organic light emitting diodes.